PERANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN WILAYAH DI ERA OTONOMI DAERAH KABUPATEN KARANGANYAR - Agustono Agustono; Ropingi Ropingi; Catur Tunggal BJP (Caraka Tani: Journal of Sustainable Agriculture, 2009)
In era regional autonomy which the regional economic development not follow the central development paradigm, but the development base on the initiative and the carrying capacity of region. The region is given the power and the freedom to develop of the direction, the object and the purpose of development with adjusted the potential and the carrying capacity. For it the region have to take the information of the potential and the contribution from economic sectors. The purpose of this research as: (1) to understand of forward linkages the agricultural sub-sector with another economic sector in Karanganyar region, (2) to understand of backward linkages the agricultural sub-sector with another economic sector in Karanganyar region and (3) to understand, what the agricultural sub-sector is leading sector in Karanganyar region?. The seconder data is used in this research. The data are taken from BPS Central Java, BAPPEDA Central Java, and BPS Karanganyar. The method is used to arrange I-O table 2005 in Karanganyar, based on to derivat from I-O table 2000 in Central Java, with the nonsurvey method as the Location Quotient approach. The tool of the analysis as (1) the linkages analysis; (2) the spreading coefficient; (3) the sensitivity of the spreading. The result of research: (1) the high value of the backward linkage of agricultural sub-sectors in Karanganyar as: animal husbandry, forestry, plantation, and fishery, (2) the low value of the backward linkage of agricultural sub-sectors in Karanganyar as the crop comodity, (3) the all agricultural sectors in Karanganyar have the low forward linkages, (4) the leading sector of Agricultural sub-sector in Karanganyar as animal husbandry, forestry, plantation and fishery. (5) the all sub-sector are not push to another economic sector in karanganyar.